The Impact of Achievement Orientation on Goal Clarity - Muhamad Taridi; Noviriani; Su'aidi Asy'ari (International School for Social and Business Studies, 2024)
Purpose: This study is to enrich the scientific paradigm in the field of Islamic education management, and to explore the effect of achievement-oriented leadership style on the goal clarity, particularly the study of organizational behavior. Study design/methodology/approach: This study employs a quantitative research approach using the survey method. The population consists of all teachers employed in a private Islamic high school in one of the provinces in Indonesia. The sample size was determined to be 120 in number, selected through the area sampling technique. Data collection utilized a questionnaire featuring a Likert scale as the primary instrument. Findings: It revealed that being achievement-oriented has a direct positive impact on goal clarity. The conclusion of this study is that the achievement-oriented, approach influences the goal clarity of Islamic Private High School in one of the provinces in Indonesia. Originality/value: In light of these criteria, the observed t-value (11.11) surpasses the tabulated t-value (1.98), leading to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). The research hypothesis asserts a direct influence of achievement-oriented heads of Islamic Private High School (X1) on the goal clarity of Islamic Private High School (X2), which is supported by the evidence.